2020
DOI: 10.3389/fgene.2020.00894
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Growth Traits in a Unique Chicken Advanced Intercross Line

Abstract: The advanced intercross line (AIL) that is created by successive generations of pseudorandom mating after the F 2 generation is a valuable resource, especially in agricultural livestock and poultry species, because it improves the precision of quantitative trait loci (QTL) mapping compared with traditional association populations by introducing more recombination events. The growth traits of broilers have significant economic value in the chicken industry, and many QTLs affecting growth traits have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Besides, a female phenotype variation of 8.2% for DPW and 6.2% for SL12 was explained by L1. These associations are also consistent with the chicken and duck SNP-based GWAS results, which indicated that SNPs located near IGF2BP1 were associated with body weight, head weight, gizzard weight, chest width, leg weight, and wing weight ( Ma et al 2019 ; Zhou et al 2018 ; Wang, Bu, et al 2020 ; Wang, Cao, et al 2020 ; Zhang, Wang, et al 2021 ). Unexpectedly, L2 allele was not found in the F2 population.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Besides, a female phenotype variation of 8.2% for DPW and 6.2% for SL12 was explained by L1. These associations are also consistent with the chicken and duck SNP-based GWAS results, which indicated that SNPs located near IGF2BP1 were associated with body weight, head weight, gizzard weight, chest width, leg weight, and wing weight ( Ma et al 2019 ; Zhou et al 2018 ; Wang, Bu, et al 2020 ; Wang, Cao, et al 2020 ; Zhang, Wang, et al 2021 ). Unexpectedly, L2 allele was not found in the F2 population.…”
Section: Resultssupporting
confidence: 87%
“…Since IGF2BP1 was also reported as the body size candidate gene using SNP-based studies ( Sheng et al 2013 ; Ma et al 2019 ; Wang, Bu, et al 2020 ; Wang, Cao, et al 2020 ; Zhang, Wang, et al 2021 ), we explored the SNPs within the region from 10 kb upstream of L1 deletion and 10 kb downstream in order to test whether any of the signal driving SNPs in previous studies could be the causal. SNP calling was done using the same 664 individual sequencing data for building the pan-genome; however, 210 individuals were excluded for the low quality of SNP calling or their heterozygous genotype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations